Integrated socio-hydrological dynamics and stakeholder views to develop conceptual water flows and salinity patterns for a polder system in coastal Bangladesh - Jampani, Mahesh; Mizan, Syed Adil; Hasib, Md. R.; Nesaruddin, Md.; Mondal, M. K.; Sena, Dipaka Ranjan; Mazid-UL Haque, T.; Alam, R.; Matheswaran, Karthikeyan (2024)
Polder systems in the Ganges delta in Bangladesh sustain intensive agricultural production and the livelihoods of about eight million people. These low-lying islands, composed mainly of alluvial sediment deposits, are critical in reducing environmental vulnerabilities against coastal erosion, flood inundation, and saltwater intrusion. The anthropogenic pressures from humans have significantly altered natural hydrological processes in this delta system, leading to numerous emerging problems. These challenges include the evolution of river channels and floodplains, water logging, sea-level rise, tidal surges, and salinity intrusion, all of which impact crop yields, agricultural productivity, and freshwater availability. With more than 160 polders spread across the region, they are predominantly used for rice cultivation in the wet season and rabi crop cultivation in the dry season. Our research aims to understand these complex dynamics of the polder system by appraising the stakeholders’ perspectives and socio-hydrological characteristics of a polder near Khulna in coastal Bangladesh. We employed a range of primary and secondary data sources, including hydrological and water quality data, inputs from government stakeholders through a workshop, and farmers' views via semi-structured surveys, and reviewed relevant literature to analyze polder heterogeneity and social dynamics. Our findings highlight the complex interplay of water availability, water use, seasonal variability, and farmers' and government stakeholder perceptions within the polder system. These insights provide a foundation for implementing a comprehensive socio-hydrological framework, which is crucial for addressing the challenges faced by the Ganges delta region. Furthermore, the results provide valuable insights into mechanisms influencing water balance, saline water intrusion or intake, crop production, livelihood and seasonal cropping practices, and dependency on groundwater during the dry season. These results can aid decision-makers in enhancing water and salinity management in these polders.